Creación de contenidos audiovisuales sobre la carrera de pedagogía de las Ciencias Experimentales: Informática implementados en un canal de YouTube. - Flores Amagua, Sabrina Pamela (2024)
The present research aims to create informative audiovisual content to improve the digital communication of the Pedagogy of Experimental Sciences Computer Science degree by implementing a YouTube channel. A three-step methodology was used to produce audiovisual content: pre-production, production, and post-production. The information was identified in preproduction, scripts were developed, and aspects such as cameras, shots, and angles were planned. The production included filming the material as planned, while in post-production, color editing, effects, transitions, and audio adjustments were carried out. Applied documentary research was used since it involved a bibliographic review of scientific articles, books, and even the official institutional websites of UNACH. The research is non-experimental and has a proactive scope aimed at the indirectly benefited population, including teachers, students, and even young people interested in being part of the degree. The research results have significantly contributed to integrating audiovisual content into a YouTube channel, dramatically improving digital communication in the course. Adapting these contents to the needs and preferences of the audience has promoted greater identification with the material and more active participation in the YouTube platform. In this sense, audiovisual production and content creation have effectively enriched digital communication in the Computer Science Pedagogy Degree, promoting research and educational dissemination